2017
DOI: 10.1002/jcp.25803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the ethno‐pharmacological studies in Iran during 2004–2016: A systematic review

Abstract: Although Iran has a deep history in herbal medicine and great heritage of ancient medical scholars, few efforts have been made to evaluate ethnopharmacological aspects of medicinal plants in this country. In the present study, the authors have reviewed all important literature about the ethnopharmacological investigations on medicinal plants used in the last decade in Iran. All provinces of Iran were categorized according to a phytogeographical division. Information was collected through bibliographic investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In Iranian Traditional Medicine, the noticeable roles of different plant families in the treatment of different illnesses are widely documented. In the recent review papers related to ethnobotanical studies published from 2004 to 2016, it was found that Labiatae was the most cited plant family (34 citations), that could be attributed to its broad distribution throughout Iran and multiple features of its plants (21). In the present work, it was found that Asteraceae is the second most reported plant family (33 citations) in Iranian Traditional Medicine.…”
Section: Nervous System Disorderssupporting
confidence: 50%
See 2 more Smart Citations
“…In Iranian Traditional Medicine, the noticeable roles of different plant families in the treatment of different illnesses are widely documented. In the recent review papers related to ethnobotanical studies published from 2004 to 2016, it was found that Labiatae was the most cited plant family (34 citations), that could be attributed to its broad distribution throughout Iran and multiple features of its plants (21). In the present work, it was found that Asteraceae is the second most reported plant family (33 citations) in Iranian Traditional Medicine.…”
Section: Nervous System Disorderssupporting
confidence: 50%
“…Thus, it enjoys a mix of cultures which is considered as a rich backbone for the expansion of ethnobotanical knowledge and plant based medicines. The study of traditional uses of medicinal plants is a major part of ethnobotany which is known as medical ethnobotany, ethnomedicine or ethnopharmacology (20)(21)(22).…”
Section: Ethnobotany In Iran: Trends and Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the plants in the Lamiaceae family have phytochemicals such as terpenes, flavonoids, and phenolic acids and have a special importance in Ethnopharmacology and phytotherapy. 10 Salvia is the -Nitric Oxide -PC12 -Astragalus jolderensis -Convolvulus commutatus -Salvia multicaulis -Griess assay largest genus of the Lamiaceae family and its species have complex and rich diversity. Furthermore, studies show that active compounds from Salvia spp.…”
Section: Introductionmentioning
confidence: 99%
“…As medicinal plants are low-priced, can enhance the resistance Afsharnasab, Kakoolaki and Mohammadidost (2016), (Kakoolaki, Akbary, Zorriehzahra, Salehi, Sepahdari, Afsharnasab, Mehrabi & Jadgal 2016, Sadeghi, Akaberi, Emami, Sobhkhizi & Sahebkar 2017 as dry powder in west and south-west of Iran, to accelerate skin wound healing (Masoudi, Ameri, Rustaiyan, Moradalizadeh & Azar 2005, Shakibaie, Pasharavesh, Khoshboo & Kaboodi 2007 and to use as a vegetable in some areas . It is a 2-year and highly branched plant and have been used in the treatment of gastric and duodenal ulcers in west of Iran for last decades (Khanahmadi & Shahrezaei 2008).…”
Section: Introductionmentioning
confidence: 99%